Stochastic modeling of aircraft flight parameters in terminal control area based on automatic dependent surveillance-broadcast (ADS-B) data. Issue 1 (August 2021) - Medianto, R; Jusuf, J; Oktafianto, R; Atiqah, R; Sembiring, J; Pasaribu, H M; Jenie, Y I; Muhammad, H
Abstract: A critical step in developing good traffic management (ATM) system simulation model is to build a kinematic model of an aircraft movement that can represent the actual conditions. This study aims to obtain flight parameters for aircraft operating in the terminal control area of Soekarno-Hatta International Airport using Automatic Dependent Surveillance-Broadcast (ADS-B) data, which is openly available on Flight Radar24. Flight parameters were measured for several flight phases, such as take-off, initial climb, climb, cruise, descend, and final approach. In addition to these flight phases, flight parameters at waypoints on the arrival and departure were also measured. Furthermore, all flight parameters are modeled stochastically through the probability distribution function (PDF) approach. The best model for each parameter is obtained using the Maximum Likelihood method (MLE) with some relevant Kosmolgrove Smirnov Test criteria. The use of ADS-B data along with the stochastic model presented in this paper provides comprehensive information on flight behavior, which can be further utilized for an aircraft simulation model of an Air Traffic Management system.